Parental perceived self-responsibility and sportspersonship in the socialization of Hong Kong's children moral behavior through sport - Pang, B.O.H.; Ha, A.S.C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Sport has been regarded as one of the successful mediums to socialize children into appropriate moral behavior. Since 2001, the Curriculum Development Council has encouraged schools to include moral and civic education as one of the major learning experiences for students` holistic development, however the extent to which these learning components are being applied by children in their daily living and during sport participation is still unclear. Thus, the intent of this study is to evaluate parental perceptions of their children`s self-responsibility (Watson, Newton & Kim, 2003) during daily living and sportspersonship in sport (Vellerand, Briere, Blanchrd & Provencher, 1997) and to examine whether their socioeconomic status influences how they perceive their child`s moral outcome. Methods The Multidimensional Sportspersonship Orientation Scale (MSOS) and the Contextual Selfresponsibility Questionnaire (CSRQ) were modified for 741 parents (Mean age=47, Fathers=252, Mothers=489) reporting their child`s sportspersonship and self-responsibility behavior. The MSOS showed high internal consistency with reliability of .90 with Hong Kong parents. One item from the CSRQ was deleted to increase the overall alpha level from .87 to .90. In addition three components of the socioeconomic status were included in the questionnaire to obtain information on parental education, occupation and income level. Results / Discussion The results showed that the mean score for parental perceived children`s sportspersonship was 3.78 and the mean score for self-responsibility was 3.19. Specifically, parents rated average scores of 3.20 in Care for Others/Goal Setting, 3.16 in Self-responsibility, and 3.21 in Self-Control/Respect, in the three dimensions of the child`s self responsibility scale. The correlation between parental perceived child`s self-responsibility and sportspersonship was significant (r=.59, p<.01). When the effects of parental socioeconomic status on their results was examined, only parental education level significantly predicted their perception of children`s self-responsibility (R2= .03, p<.01). Conclusions In conclusion, Hong Kong parents generally regarded that their children are able to demonstrate sportspersonship in sporting events and self-responsibility in daily living. The findings will help raise awareness of the inclusion of parental involvement and perception on sport-related curriculum implementation with regards to children`s moral behavior.